A novel ember shower simulator for assessing performance of low porosity screens at high wind speeds against firebrand attacks. (July 2016) - Sharifian, Ahmad; Hashempour, Javad
Previous studies have shown the effectiveness of low porosity and double-layer screens against radiant heat flux from fires. The performance of screens against firebrand attack is also required to be assessed prior to making a decision on their possible application in wildland fire prone areas. The available laboratory-scale devices simulate firebrands at wind speeds less than those of severe firebrand attacks. A relatively low cost, laboratory-scale fire ember shower simulator has been designed and manufactured in-house. The simulator is able to assess the performance of low porosity screens at high wind speeds without any reverse flow and possible consequent safety hazards and offers reasonable control over the size and mass of the generated firebrands.